2018
DOI: 10.7547/17-026
|View full text |Cite
|
Sign up to set email alerts
|

Foot Mobilization and Exercise Program Combined with Toe Separator Improves Outcomes in Women with Moderate Hallux Valgus at 1-Year Follow-up

Abstract: Background: Few studies have documented the outcome of conservative treatment of hallux valgus deformities on pain and muscle strength. We sought to determine the effects of foot mobilization and exercise, combined with a toe separator, on symptomatic moderate hallux valgus in female patients. Methods: As part of the randomized clinical trial, 56 women with moderate hallux valgus were randomly assigned to receive 36 sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
3
28
0
1
Order By: Relevance
“…In a deformity, the activity of the intrinsic muscles of the foot (the abductor hallucis muscle and the adductor hallucis muscle [47]) is imbalanced [47,49]. This malfunction is a factor of hallux valgus development [48]. From the relation between HVA and TAH seen in our results, we would suggest the same management methods in increased TAH by targeting the intrinsic muscles.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In a deformity, the activity of the intrinsic muscles of the foot (the abductor hallucis muscle and the adductor hallucis muscle [47]) is imbalanced [47,49]. This malfunction is a factor of hallux valgus development [48]. From the relation between HVA and TAH seen in our results, we would suggest the same management methods in increased TAH by targeting the intrinsic muscles.…”
Section: Discussionmentioning
confidence: 50%
“…Past publications on interventions for hallux valgus depended on the severity and duration of the deformity, the level of pain, and the age of the individual [9,46], ranging from surgery to orthotics [7] and specific exercises [47]. One study mentioned foot mobilization such as: manual mobilization focusing on flexion and caudal sliding of the metatarsophalangeal joints, tarsals, subtalar and ankle joint and exercise (hallux plantar flexion strengthening exercises, hallux abduction strengthening exercises and towel curl exercise) to increase the foot's joints range of motion and toe grip strength and decrease pain [48]. Others mentioned toe-spreadout exercise [47,49] and short-foot exercise [49].…”
Section: Discussionmentioning
confidence: 99%
“…22,23 AOFAS((American Orthopaedic Foot and Ankle Society) scores have been described in previous reports which could be an effective tool to evaluated the foot function. 24,25 In our study there have only two researches reported preoperative and postoperative AOFAS data,and the result show that there have no significant difference between Scarf and Chevron osteotomy,but there is need more data to support this result in the future.…”
Section: Literature Searchmentioning
confidence: 68%
“…Therefore, stretching of iliotibial band should be considered during rehabilitation of the hallux valgus. Abdalbary [22] reported that Bunion stretch increased the range of motion of greater toe and lengthened the surrounding tissue which helped in decrease the hallux valgus deformity. Again, Kim et al [23,24] opined that strengthening of the adductor halluces and abductor halluces could prevent a hallux valgus and could be helpful to correct the deformity.…”
Section: Discussionmentioning
confidence: 99%